Hormonal parameters and embryological outcomes of in vitro fertilisation/intra cytoplasmic sperm injection cycles in women using dydrogesterone for the prevention of premature luteinizing hormone surge during ovarian stimulation - Irina E. Korneeva; Alla I. Kovalchuk; Tatiana A. Nazarenko; Elena V. Mityurina; Svetlana G. Perminova; Aleksei V. Bachurin; Tatiana Yu. Ivanets (IP Berlin A.V., 2022)
Aim. To evaluate the hormonal parameters and embryological outcomes of an ovarian stimulation protocol using dydrogesterone to prevent the premature LH surge in IVF/ICSI programmes. Materials and methods. A prospective study randomised, including 79 women with normal ovarian reserve undergoing ovarian stimulation for IVF/ICSI with recombinant FSH (rFSH) from Day 2 or 3 of the menstrual cycle. To prevent the premature LH surge, participants in Group 1 (n=38) received oral dydrogesterone 20 mg/day from the start of ovarian stimulation until the day of ovulation trigger administration. Participants in Group 2 (n=41) received a GnRH antagonist. We evaluated the starting and total dose of gonadotropins, duration of stimulation, serum levels of LH, oestradiol and progesterone on Day 1 and 6 of stimulation and the day of trigger administration, number of retrieved and mature oocytes, fertilization rate, and the number of blastocysts and cryopreserved embryos. Results. There were no significant differences in most hormonal parameters, characteristics of the ovarian stimulation and embryological outcomes between the two groups. Serum levels of progesterone in the dydrogesterone arm were higher than in the GnRH antagonist arm (2.3 nmol/l [2.03.4] vs 1.5 [1.02.4] nmol/l; p=0.026), but without any impact on the embryological outcomes. Conclusion. Prevention of premature LH surge in ovarian stimulation cycles using oral dydrogesterone may represent a convenient alternative to the conventional use of GnRH antagonists, reducing the number of required injections and potentially increasing the convenience in patients who are not planning a fresh embryo transfer.